Analyses microbiologiques, biochimiques et biotechnologiques des levures issues du cépage Cinsault cultivé dans la commune Ben Abdelmalek Ramdane (Wilaya de Mostaganem) - BELMAZIZ, Meriem; DJALAL, Faouzia (My University, 2017)
Defined as the fruit of the vine, the most widely grown grapes in the world. It is considered to be a core of a large number of levuriennes species habitats. So our study aimed to isolate, purify and characterize species of yeasts from the grape Cinsault harvested of the commune Ben Abdelmalek Ramdane wilaya of Mostaganem. We performed microscopic and macroscopic, tests and other tests of sporulation, ability to the filamentisation, biochemical and biotechnological testing, which showed the presence of 5 strains levuriennes. These 5 strains of levuriennes are characterized by significant performance of CO2 and ethanol production, as well as the presence of the enzyme invertase.
Keywords: grape; yeasts; Cinsault; CO2; Ethanol; Invertase; raisin; levures